Assessing Public Financing for Nutrition in Sri Lanka (2014-2018) - World Bank (World Bank, Washington, DC, 2021)
Relative to other countries in the region, Sri Lanka has invested modestly on nutrition programs and interventions. Current nutrition programs in Sri Lanka need to be reviewed, both in terms of design and beneficiaries, and prioritized in terms of effectiveness, cost-effectiveness, and good practices. The resource allocation for nutrition-specific interventions deserves revisiting, considering that these investments are driven by the nutrition agenda, and are more responsive to real needs. Mainstreaming nutrition in other sectors is also necessary, to ensure more voice in decision making, and to strengthen multisectoral engagement and coordination in nutrition. Targeted programs can be more cost-effective than blanket coverage as long as the targets are well selected, and a prioritization exercise is conducted to consider negative side effects. Nutrition awareness-raising programs and educational and promotive activities may deserve more allocation.